Evaluation of Pooled Sample Analysis Strategy for SARS-CoV-2 RT-PCR Tests in Diagnosis and Screening of COVID-19 (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: The recent outbreak of COVID-19 is a serious global concern. The emergence of SARS-CoV-2 led to a current pandemic of unprecedented levels. Early detection of the infection and prompt isolation of the cases are fundamental for containment of such outbreak. By this time, healthcare systems are facing shortages of reagents for diagnosing this disease. In this context, sample pooling can be an effective strategy to overcome this situation. This study aimed to evaluate the effectiveness of sample pooling strategy for RT-PCR tests for diagnosing and screening of COVID- 19 in mass population.Methods: A cross-sectional study was performed at the COVID-19 laboratory of Armed Forces Institute of Pathology of Bangladesh to evaluate the efficacy of sample pooling technique for detecting SARS-CoV-2 infection. In this laboratory, nasopharyngeal and oropharyngeal swabs were taken for the RT-PCR test to diagnose COVID-19. For each patient, both nasopharyngeal and oropharyngeal samples were taken and then mixed to make a single sample. Pooling was performed from the samples collected from 1 April 2020 to 30 April 2020. Total 350 samples were distributed randomly in 70 pools, so that each pool contains 5 samples. Positive pools were deconvulated and each sample was tested separately. Screening was performed by using RT-PCR targeting the ORF-1ab Region and N-gene.Results: Out of 70 pools 16 (22.85%) were found positive. Eighty samples of these 16 pools were tested individually and 21 (21/80, 26.25%) samples were found positive. All the positive pools were reproducible with testing of the individual samples of that pool (100%).Conclusion: Strategies of using pooled samples for screening may facilitate detection of early community transmission of SARS-CoV-2 and enable timely implementation of appropriate infection control measures to reduce spread.J Bangladesh Coll Phys Surg 2020; 38(0): 16-20